Implementasi Algoritma FP-Growth Pada Pengenalan Pola Penjualan - Nurasiah, Nurasiah (TIN: Terapan Informatika Nusantara, 2021)
Data Mining is a series of processes to extract additional value in the form of information that has been known manually from a database by extracting patterns from data with the aim of manipulating data into more valuable information obtained by extracting and extracting patterns important or pull the data contained in the database. Data Mining technique has various kinds of algorithms and techniques for solving problems related to data, one of which is the FP-Growth algorithm and the association rule technique. The information displayed using the association rule technique, which displays the value of support and confidence from each data mining process. With the FP-Growth algorithm, it is proven from the results of the tests carried out, the FP-Growth algorithm and the association rule technique run as expected and can be implemented in this Data Mining